Banks and negative interest rates - Florian Heider; Farzad Saidi; Glenn Schepens (European Central Bank (ECB), 2021)
In this paper, we survey the nascent literature on the transmission of negative policy rates. We discuss the theory of how the transmission depends on bank balance sheets, and how this changes once policy rates become negative. We review the growing evidence that negative policy rates are special because the pass-through to banks' retail deposit rates is hindered by a zero lower bound. We summarize existing work on the impact of negative rates on banks' lending and securities portfolios, and the consequences for the real economy. Finally, we discuss the role of different "initial" conditions when the policy rate becomes negative, and potential interactions between negative policy rates and other unconventional monetary policies.
Keywords: E44; E52; E58; G20; G21; 330; deposits; negative interest rates; zero lower bound; bank lending; bank risktaking; euro-area heterogeneity